PENYELESAIAN PERKARA OLEH LEMBAGA ADAT MENGENAI PERKELAHIAN ANTAR SESAMA KRAMA DESA YANG TERJADI DI DESA PAKRAMAN SARASEDA - Miswadanta Pradaksa, Ida Bagus; Putri M.E Purwani, Sagung (Kertha Desa; Vol. 02, No. 01, Januari 2014, 2014)
Resolution of the matter by the custom institutions about fights between fellow krama village which happened in Saraseda pakraman village. Written with the purpose to know the existence of juridical authority in pakraman village along with in ordinances custom case resolution happens at pakraman village area surroundings. Problems that arise are whether the completion of the matter have been reflecting the principle of consensus in the deliberations, so that its application in practice is expected to restore the disruption of the balance of relations in society. The research method used is the empirical research that revealed the law society’s behavior in real life, especially in resolving the legal issues that it faces. Based on the terms in awig-awig pakraman village, custom case were resolved by custom prajuru Saraseda Pakraman Village through paruman as an institution of the highest consensus in the deliberations in the village. In case that happens paruman discussed and sought solutions as well as custom sanctions sangaskara danda dropped the verdict to offender.
Keywords: Pakraman Village, Custom Case, Custom Prajuru, Awig-Awig